Analysis of asymptotic for a model of nonlinear oscillations of the two string - Lavcel-Budko, Olga; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2015)
The mathematical model of two strings nonlinear oscillations is presented. To find uniformly valid in a long time interval asymptotic solution of the problem an averaging scheme is constructed.
Keywords: resonance; asymptotic methods; nonlinear waves; averaging